Analisis Pembentukan Kemandirian pada Anak Usia Dini Melalui Kurikulum Pendidikan Agama Islam Terpadu di TK IT Rabbani Quran School Babahrot - Widia Astuti; Rohinah Rohinah; Heldanita Heldanita; Mohd. Reza Pahlevi (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2022)
An integrated Islamic school is a school that implements a curriculum to optimally integrate religious and general sciences. Independence is the ability in a person to act and do something so that it creates a positive attitude of responsibility in others. This research wants to know the formation of independence in early childhood through the PAI curriculum. For further research, it is possible to combine religious and public schools. The method used in this research is a descriptive qualitative approach. Sources of data obtained from field studies (Field Research), which comes from written data and interviews. Based on the results of research at TK IT Rabbani Quran School Babahrot on the Analysis of Independence Formation in Early Childhood Through the Integrated Islamic Religious Education Curriculum at TKIT Rabbani Quran School Babahrot Independence is a description of the school's vision. The school's vision is revealed in the form of a mission, curriculum. Islamic education is one of the most important educations that must be given to children from an early age with the aim of forming a strong Islamic generation with elements of aqidah, morals, and worship.ABSTRAKSekolah Islam terpadu merupakan sekolah yang mengimplementasikan kurikulum untuk memadukan secara maksimal antara ilmu agama dan ilmu umum. Kemandirian merupakan kemampuan dalam diri seseorang untuk bertindak dan melakukan sesuatu sehingga menimbulkan sikap tanggungjawab  yang bersifat positif pada orang lain.  Peneitian ini ingin mengetaui pembentukan kemandirian pada anak usia dini melalui kurikulu PAI.  Untuk peneitian selanjutnya bisa mengabungkan antara sekolah yang agama dan umum. Metode yang digunakan dalam penelitian ini pendekatan kualitatif deskriptif. Sumber data diperoleh dari studi lapangan (Field Research), yang bersumber dari data tertulis dan hasil wawancara. Berdasarkan hasil penelitian di TK IT Rabbani Quran School Babahrot tentang Analisis Pembentukan Kemandirian pada Anak Usia Dini Melalui Kurikulum Pendidikan Agama Islam Terpadu di TKIT Rabbani Quran School Babahrot Kemandirian merupakan penjabaran visi sekolah. Visi sekolah tersebut diturunkan dalam bentuk misi, kurikulum. Pendidikan Agama Islam merupakan salah satu pendidikan yang amat penting yang harus diberikan kepada anak sejak usia dini dengan tujuan agar terbentuk generasi Islam yang kokoh dengan unsur aqidah, akhlak, dan ibadahnya.